Social representations of law, justice and injustice: A study with Argentinean and Brazilian adolescents - Shimizu, A. D.; Menin, MSD (Foundation Advancement Psychology, 2004)
This study aims to analyze the main social representations of law, justice and injustice preseneted by Argentinean and Brazilian youngsters. The Brazilian group consisted of 621 polled of three different regions-Floriano/PI, Erechim/RS, and Marilia/SP. From Argentina, 200 youngsters of Avellanedacity (Buenos Aires metropolitan region) participated. All the samples were proportionally divided according to the kind of school (public or private) and the school year attented (8(th) grade and 11(th) grade, considering the equivalent grade in Argentina). The data collection technique consisted of semi directed questionnaire composed by the free evocation of words technique. The procedure used to evaluate the results was the Analysis Correspondence Method (ANACOR). The results demonstrate important variations related to the youngster' nationality and they were discussed so that the preseneted representations were contextualized.
Keywords: social representations theory; free evocation of words; law-justice-injustice